Cardinal Newman's Phenomenology of Religious Belief - Newman, Jay (Religious studies, 1974)
While one of John Henry Newman's principal aims in the Grammar of Assent is to explain how men can give a real assent' to the existence of God, the major part of the actual phenomenology of religious belief in the work is concentrated in the fifth of its ten chapters. Unfortunately, this section of the essay has been overshadowed by the preliminary distinction between real and notional apprehension and by the later invocation of the illative sense; but perhaps the time is now ripe for a closer examination of this central part of Newman's philosophy of religion, which is in many ways the key to the successes and failures of Newman's new method in philosophical theology.